The Teaching Presence with Audiovisual Media in Virtual Scenarios in Higher Education in Arequipa - Vera-Ninacondor, Carlos Pedro; Ortiz-Valderrama, Cecilia del Carmen; Aguilar-Gonzales, Jose Luis; Gamarra-Castellanos, María Elena (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The innovation processes of information technologies in higher education didactics have not been synchronized processes technological transformations do not go in parallel with pedagogical adaptations, however, the violent irruption of the COVI19 pandemic made this distance evident; the objective of the research is to identify the value of the teaching presence with audiovisual media in the virtual auditorium identifying the relationships of motivation and confidence of students in order to rethink an optimal virtual scenario. The study analyzes the levels of confidence and motivations generated by the visual perception of the teacher, the participation of 127 students of communication sciences; the temporal perspective is descriptive transectional, with a quantitative approach. Among the relevant findings, a high level of indifference of the students is perceived, in turn, the teacher's response has a pessimistic ingredient, the proportionality of his presence is lower and the tendency is limited,